Automated functional upper limb evaluation of patients with Friedreich ataxia using serious games rehabilitation exercises - Bonnechère, Bruno; Jansen, Bart; Haack, Inès; Omelina, Lubos; Feipel, Véronique; Van Sint Jan, Serge; Pandolfo, Massimo (Journal of neuroengineering and rehabilitation, 2018)
Background Friedreich ataxia (FRDA) is a disease with neurological and systemic involvement. Clinical assessment tools commonly used for FRDA become less effective in evaluating decay in patients with advanced FRDA, particularly when they are in a wheelchair. Further motor worsening mainly impairs upper limb function. In this study, we tested if serious games (SG) developed for rehabilitation can be used as an assessment tool for upper limb function even in patients with advanced FRDA. Methods A specific SG has been developed for physical rehabilitation of patients suffering from neurologic diseases. The use of this SG, coupled with Kinect sensor, has been validated to perform functional evaluation of the upper limbs with healthy subjects across lifespan. Twenty-seven FRDA patients were included in the study. Patients were invited to perform upper limb rehabilitation exercises embedded in SG. Motions were recorded by the Kinect and clinically relevant parameters were extracted from the collected motions. We tested if the existence of correlations between the scores from the serious games and the severity of the disease using clinical assessment tools commonly used for FRDA. Results of patients were compared with a group a healthy subjects of similar age. Results Very highly significant differences were found for time required to perform the exercise (increase of 76%, t(68) = 7.22, P < 0.001) and for accuracy (decrease of 6%, t(68) = − 3.69, P < 0.001) between patients and healthy subjects. Concerning the patients significant correlations were found between age and time ( R = 0.65, p = 0.015), accuracy ( R = − 0.75, p = 0.004) and the total displacement of upper limbs. ( R = 0.55, p = 0.031). Statistically significant correlations were found between the age of diagnosis and speed related parameters. Conclusions The results of this study indicate that SG reliably captures motor impairment of FRDA patients due to cerebellar and pyramidal involvement. Results also show that functional evaluation of FRDA patients can be performed during rehabilitation therapy embedded in games with the patient seated in a wheelchair. Trial registration The study was approved as a component of the EFACTS study ( Clinicaltrials.gov identifier NCT02069509 , registered May 2010) by the local institutional Ethics Committee (ref. P2010/132).